Answer:
b = (d-c)/a
Step-by-step explanation:
ab+c=d
Subtract c from each side
ab+c-c=d-c
ab = d-c
Divide by a
ab/a = (d-c)/a
b = (d-c)/a
Answer:
Step-by-step explanation:
1,8
5,7
2,3
y = -1/2x + 5 should be your equation because it is 5 ft above sea level and its eroding, or going down, 1 ft per 20 years. So every year, the sand dune erodes 1/20 ft more.
Hope this helps!
to solve for the dimensions (x+7)(x+2)=66,
we can first use the foiling method to simplify the left side.
x^2 + 2x + 7x + 14 = 66
x^2 + 9x + 14 = 66
now, subtract 66 from both sides.
x^2 + 9x - 52 = 0
now, split this into two parentheses.
(x + 13)(x - 4)
since the root of -13 would give you negative values, x=4. This means that the dimensions of the rectangle are 11 and 6.
As per this theorem the two triangles are congruent if two angles and a side not between these two angles of one triangle are congruent to two corresponding angles and the corresponding side not between the angles of the other triangle.